Compliance behavior in networks: Evidence from a field experiment - Drago, F., Mengel, F. and Traxler, C. (American Economic Journal: Applied Economics)
This paper studies the spread of compliance behavior in neighborhood networks in Austria. We exploit a field experiment that varied the content of mailings sent to potential evaders of TV license fees. The data reveal a strong treatment spillover: untreated households are more likely to switch from evasion to compliance in response to mailings received by their network neighbors. Digging deeper into the properties of the spillover, we find that it is concentrated among close neighbors of the targets and increases with the treated households' diffusion centrality. Local concentration of equally treated households implies a lower spillover. - Reproduced
Keywords: Compliance behavior, Neighborhood networks, Social learning, Spillover evasion, Field experiment